INFLUENCE OF APPLYING THE DIFFERENT ACIDS FOR ADJUSTING THE DYEBATH pH IN THE PROCESS OF DYEING THE POLYESTER KNITWEAR WITH DISPERSE YELLOW 3 - N. Miljković, M.; M. Purenović, M.; M. Petrović, M. (Journal of Engineering & Processing Management, 2010)
The influence of using formic, oxalic, citric and tartaric acid for adjusting the dyebath pH upon the dyeability of polyester knitwear dyed with Disperse Yellow 3 was investigated. CIELAB coordinates of the knitwear samples dyed with the addition of tested acids were assessed and compared to those dyed with the addition of acetic acid. The differences in dyeabilities obtained with the addition of citric and oxalic acid are acceptable according to both M&S 83A and CMC (2:1) standard and the difference in dyeability obtained with the addition of tartaric acid is acceptable according to CMC(2:1) standard in comparation to the dyeability obtained with the addition of acetic acid, at dye concentration of 1%. For the dye concentration of 2%, acceptable difference in dyeability, in comparation to the dyeability obtained with the addition of acetic acid, according to both M&S 83A and CMC (2:1) standard, was obtained with the addition of tartaric acid.